The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1111/jasp.12326
|View full text |Cite
|
Sign up to set email alerts
|

When do women respond against discrimination? Exploring factors of subtlety, form, and focus

Abstract: We examined the personal-group discrimination discrepancy (PGDD), the tendency for women to recognize that others encounter sexism while simultaneously minimizing their own personal experiences with sexism, and the degree to which it (a) applies to all manifestations of discrimination, and (b) extends beyond perceptions of discrimination to taking action against it. Our findings replicated the PGDD when it comes to perceptions of discrimination, but this effect was reversed for behavioral action such that wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 32 publications
0
21
1
Order By: Relevance
“…Although we realize this assertion may be met with some controversy and skepticism, there is recent empirical work that supports our view. Indeed, Lindsey and colleagues (2015) showed that women could reliably distinguish between factors of subtlety and formality when deciding how they would respond to scenarios depicting various instances of discrimination. Specifically, the findings revealed that although there were no differences in women's abilities to detect interpersonal versus formal discrimination, women were more likely to detect overt as compared with subtle manifestations of discrimination.…”
Section: What Is Subtle Discrimination?mentioning
confidence: 99%
See 2 more Smart Citations
“…Although we realize this assertion may be met with some controversy and skepticism, there is recent empirical work that supports our view. Indeed, Lindsey and colleagues (2015) showed that women could reliably distinguish between factors of subtlety and formality when deciding how they would respond to scenarios depicting various instances of discrimination. Specifically, the findings revealed that although there were no differences in women's abilities to detect interpersonal versus formal discrimination, women were more likely to detect overt as compared with subtle manifestations of discrimination.…”
Section: What Is Subtle Discrimination?mentioning
confidence: 99%
“…To the extent that subtlety and formality reflect the same construct, one would expect to observe similar effects across dependent variables of interest, as opposed to the differing effects that the authors observed here. In an effort to examine whether women's actual experiences also varied across these dimensions of discrimination, Lindsey and colleagues (2015) conducted a follow-up study in which they asked women to recall discriminatory incidents that they had experienced or witnessed in the workplace. These incidents were then rated by two independent coders with regard to subtlety and formality.…”
Section: What Is Subtle Discrimination?mentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that disenfranchised populations such as women [ 30 ], racial minorities [ 31 ], religious minorities [ 32 ], sexual orientation minorities, [ 33 ] and older employees [ 34 ] endure different forms of mistreatment at work. For example, past work details that marginalized employees are perceived as incompetent [ 35 ] and perceive greater instances of both formal and interpersonal discrimination from others as compared to majority status employees [ 36 ]. This perceived or recognized interpersonal mistreatment at work relates to a variety of negative job-related outcomes such as lower commitment, lower job satisfaction, greater work tension, less engagement, higher withdrawal, greater depressive symptoms, and greater job insecurity [ 35 , 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…We focus our investigation of whether perceived centrality shapes intergroup dynamics on the workplace context because the expression of sexism in everyday interactions between coworkers continues to be prevalent ( Ely et al, 2006 ; Swim et al, 2001 ). We focus on women’s desire to confront a sexist comment because women must want to engage in this action before actually confronting ( Ashburn-Nardo et al., 2008 ; Lindsey et al, 2015 ). Past research has focused on how individual characteristics (e.g., optimism, Kaiser & Miller, 2001 , 2004 ; hardiness, Foster & Dion, 2004 ; trait activism, Hyers, 2007 ; Swim & Hyers, 1999 ) and situational factors (e.g., formal power, Ashburn-Nardo et al, 2014 ; Woodzicka & LaFrance, 2005 ; salient costs, Shelton & Stewart, 2004 ; public contexts, Stangor et al., 2002 ; risk to standing, Kaiser & Miller, 2001 , 2004 ) can restrict confronting.…”
Section: Introductionmentioning
confidence: 99%